Identifying Facilitators and Barriers for Patient Safety in a Medicine Label Design System Using Patient Simulation and Interviews. Issue 4 (December 2016) - Dieckmann, Peter; Clemmensen, Marianne Hald; Sørensen, Trine Kart; Kunstek, Pina; Hellebek, Annemarie
Abstract : Objectives: Medicine label design plays an important role in improving patient safety. This study aimed at identifying facilitators and barriers in a medicine label system to prevent medication errors in clinical use by health care professionals. Methods: The study design is qualitative and exploratory, with a convenience sample of 10 nurses and 10 physicians from different acute care specialties working in hospitals in the Capital Region of Denmark. In 2 patient simulation scenarios and a sorting task, the participants selected the medicines from a range of ampules, vials, and infusion bags. After each scenario and in the end of the study, the participants were interviewed. Notes were validated with the participants, and content was analyzed. Results: The label design benefited from the standardized construction of the labels, the clear layout and font, and some warning signs. The complexity of the system and some inconsistencies (different meaning of colors) posed challenges, when considered with the actual application context, in which there is little time to get familiar with the design features. Conclusions: For optimizing medicine labels and obtaining the full benefit of label design features on patient safety, it is necessary to consider the context in which they are used.